Model of appropriation and use of audiovisual/digital media in rural intercultural educational communities in the Araucanía region, Chile. (Praxis Educativa, 2023)
The purpose of this study was to develop a model of appropriation and use of audiovisual/digital media in rural intercultural schools applying a modeling methodology with a naturalistic approach. Teachers, directors and students from eight schools in the Araucanía region participated. In addition, a questionnaire was applied to forty-nine teachers from intercultural rural schools in the region. The elaborated model establishes that the process of changes that Chilean society is experiencing, consisting of a growing and accelerated digitization of the world of life and work, configures a complex context in which teachers deploy their educational praxis and that is conditioning the Appropriation and Use that they make of audiovisual/digital media, both in their institutional work and in their daily lives. Among other aspects, the appropriation and use of these media is expressed in the active role of the teachers in the production of their own audiovisual material, orienting it mainly to the empowerment of Being Mapuche.
Keywords: digitization, school, school-community relationship, pandemic, rural environment